Propolis polyphenols: A review on the composition and anti-obesity mechanism of different types of propolis polyphenols - Zhu, Liuying; Zhang, Jinwu; Yang, Hui; Li, Guangyan; Li, Hongyan; Deng, Zeyuan; Zhang, Bing (Frontiers in Nutrition, 2023)
Obesity, one of the most common nutritional diseases worldwide, can lead to dyslipidemia, high blood sugar, high blood pressure, and inflammation. Some drugs have been developed to ameliorate obesity. However, these drugs may cause serious side effects. Therefore, there is an urgent need for alternative "natural" remedies including propolis. Studies have found that propolis has excellent anti-obesity activity in in vitro and in vivo models during the past decades, of which polyphenols are the key component in regulating weight loss. This review focused on the different polyphenol compositions of propolis from different regions and plants, the evidence for the anti-obesity effects of different types of propolis and its derivatives, discussed the impact of propolis polyphenols on obesity related signal pathways, and proposed the molecular mechanism of how propolis polyphenols affect these signal pathways. For example, propolis and its derivatives regulate lipid metabolism related proteins, such as PPARα, PPARγ, SREBP-1&2 and HMG CoA etc., destroy the formation of CREB/CRTC2 transcription complex, activate Nrf2 pathway or inhibit protein kinase IKK ε/ TBK1, thereby affecting fat production and lipid metabolism; The effects of propolis on adipokines (adiponectin, leptin and inflammatory factors) were discussed. Additionally, the mechanism of polyphenols in propolis promoting the browning of adipose tissues and the relationship between intestinal microorganisms was summarized. These information may be of value to better understand how specific propolis polyphenols interact with specific signaling pathways and help guide the development of new drugs to combat obesity and related metabolic diseases.